Educational dilemmas : debate and diversity - Watson, Keith, 1939-; Modgil, Celia; Modgil, Sohan (Cassell, 1997)
This text addresses the reforms in the financial and administrative structure of higher education, government intervention in introducing new managerial techniques and quality audits, and the implications of these changes for both academics and administrators. It is one of a series of four volumes which look at the educational dilemmas facing governments, professional educators and practising administrators in the current climate in education. The issues are addressed from international and comparative perspectives.